Effect of Different Silane Coupling Agents on the Bond Strength between Hydrogen Peroxide-Etched Epoxy-Based- Fiber-Reinforced Post and Composite Resin Core - Sarah Adwani; Emad Elsubeihi; Ahmad Zebari; May Aljanahi; Keyvan Moharamzadeh; Haitham Elbishari (MDPI AG, 2023)
The aim of the study was to evaluate the effect of various silane coupling agents on the micro-push-out bond strength between a hydrogen peroxide-etched epoxy-based fiber-reinforced post and composite resin core. Seventy-five cross-linked epoxy-based fiber-reinforced posts were etched with 24% hydrogen peroxide for 10 min. Then they were divided into five groups according to various silane coupling agents and bonded to a composite core. A Universal Testing Machine was utilized to evaluate the push-out bond strength. In addition, all groups' modes of failure were assessed. The push-out bond strength data in MPa were analyzed using ANOVA and a Tukey HSD post hoc test to reveal any difference between the groups. Results revealed that the application of a two-bottle silane coupling agent exhibited the highest bond strength, while the application of a one-bottle silane coupling agent demonstrated the lowest bond strength for a hydrogen peroxide-etched fiber post bonded to a composite core material, which was statistically significant (p < 0.05). The strongest association with the highest bond strength was found with the two-bottle silane coupling agent when compared to the one-bottle. The study highlighted that the application of a silane-coupling agent may affect the bond strength between composite and epoxy-based fiber-reinforced posts.